"I Think That's the Norma Rae in Me": Teachers' Perceptions of Outcomes for the 2018 Oklahoma Teacher Walkout. Issue 4 (2nd October 2022) - Schachle, Jessica L.
ABSTRACT: In 2018, teacher walkouts were erupting across the United States due to a lack of funding and teacher pay. While the success of these walkouts varied by state, the Oklahoma teacher walkout did not achieve all its goals, as state lawmakers were not willing to establish a consistent means of funding for education. Despite this defeat, participants reported that they found their participation meaningful. Why? This article utilizes 20 in-depth interviews to show that movement participants sometimes view collective identity and social ties as important movement outcomes. Previous studies focused on movement wins and losses have highlighted that identity and social ties can be framed as key movement outcomes. However, literature has not considered how, despite notable losses, movement participants still acknowledge that they are happy to have participated in the movement as long as they gain a personal or biographical outcome. Furthermore, literature has yet to address how these outcomes manifest in teacher movements. By including considerations for biographical and personal outcomes for movements that fail to achieve notable legislative changes, future research will be able to highlight the importance of participant-identified satisfaction. Additionally, these outcomes may be particularly important to consider in the context of teacher walkouts because fringe benefits can contribute to enhanced feelings of solidarity that may lay the groundwork for future movements.